Low vision rehabilitation: An incipient issue - Oviedo Cáceres, María del Pilar; Arias Pineda, Karen Natalia; Palencia Flórez, Diana Cristina (Revista Cuidarte, 2023)
Introduction: People with low vision need a vision rehabilitation process that allows them to optimize their remaining vision and thus mitigate the impact of the disability. Objective: To describe the conditions for access to vision rehabilitation in Bucaramanga and its metropolitan area. Materials and Methods: A collective case study was conducted by taking elements from phenomenology. The theoretical position of Andersen and collaborators was assumed. Semi-structured interviews were conducted with 11 patients and professionals involved in care and rehabilitation residing in municipalities in the metropolitan area of Bucaramanga. The analysis was done in three stages: discovery, coding, and interpretation of the data. Results: Two categories emerge from the study: 1) Vision rehabilitation: An incipient issue, and 2) People with low vision experience in low vision management care processes; the latter with the following subcategories: Failures in the identification and orientation to low vision management and difficulties in attending clinical care and accessing devices. Discussion: Describing the conditions for accessing rehabilitation services can contribute to designing intervention strategies to address the identified barriers. Conclusions: The consequences of low vision can be mitigated by accessing rehabilitation processes; however, in the four participating municipalities, people face multiple barriers to rehabilitation. This situation evidences the need to establish mechanisms that allow people with visual impairments to exercise their right to health.How to cite this article: Oviedo-Cáceres Maria del Pilar, Arias-Pineda Karen Natalia, Palencia-Flórez Diana Cristina. Rehabilitación de la baja visión: Un asunto incipiente. Revista Cuidarte. 2023;14(2):e2665. http://dx.doi.org/10.15649/cuidarte.2665
Keywords: Vision; Low; Health Services; Rehabilitation; Access of Health Services